Uji Aktivitas Ekstrak Biji Caesalpinia Sp terhadap Jumlah Eritrosit Mus musculus yang Diinfeksi Plasmodium berghei serta Implementasinya dalam Pembelajaran Kimia - Nurleli Nurleli; Agus Sundaryono; Aceng Ruyani (PendIPA Journal of Science Education, 2018)
AbstraCT[Activity test of Caesalpinia sp seed extract on erythrocytes amount of Mus musculus infected by Plasmodium berghei and its implementation in chemistry learning]. The aims of this study were to (1) determine the activity of seed extract (Caesalpinia sp) on the number of Erythrocytes of M. Musculus of Swiss Webster Strain infected by P.berghei, (2) Find  the active compounds obtained from the isolation of Caesalpinia sp seed extract (3) Find the differences in student learning outcomes about the separation of secondary metabolites using thin layer chromatography (TLC) which is taught in chemistry learning by using LKS. In this study Caesalpinia sp seed extract was purified by thin layer chromatography and column coromatography, and was identified by IR and 1H-NMR spectroscopy. M. musculus infected with P. berghei was given Caesalpinia sp seed extract at a dose of 0.028 g/Kgbb, 0.056 g/Kgbb, and 0.084 g / Kgbb by gavage, while the positive control group was given Kloroquin diphosphate, negative control was given olive oil. Caesalpinia sp seed extract with a dose of 0.056 g/Kgbb inhibited the highest plasmodium, which was 42.89% and even exceeded the malaria drug commonly used chloroquin diphosphate 29.85%. Caesalpinia sp seed extract capable of reducing plasmodium in erythrocytes is also able to increase the number of uninfected erythrocytes. The active compounds obtained from the isolation of Caesalpinia sp seed extract are alkaloids, flavonoids, saponins, and terpenoids. In the implementation of extracurricular group learning is taught by using worksheets. There are significant differences where the average posttest score is 88.67 and the average pretest is 32.1. Keywords: Caesalpinia Sp.; Erythrocyte; Plasmodium berghei; Mus muscullus; Student working sheet.